The Member of Parliament and his information - Barker, Anthony P.; Rush, Michael (London : Allen & Unwin, 1970)
This is a book about British Members of Parliament and their work. It is the first such book to be based on a survey of a sample of Members which asks them many questions about their duties and their opinions of their work and of their place in the British political system.
For Political and Economic Planning, and the study of Parliament Group.
Includes bibliographical footnotes and index.
kjo 17/01/2019; ne 27/06/2019
Loans
Keywords: Legislators; Legislative reference bureaus